Effects of Age Among Elderly Cancer Patients on Breakthrough Pain Management with Sublingual Fentanyl Tablets - Jordi Guitart; María Isabel Vargas; Vicente De Sanctis; Jordi Folch; Rafael Salazar; José Fuentes; Joan Coma; Julia Ferreras; Jordi Moya; Albert Tomás; Pere Estivill; Francisco Rodelas; et al. (Adis, Springer Healthcare, 2019)
Abstract Introduction Sublingual fentanyl tablets (SFTs) have been shown to be a safe and effective option in controlling breakthrough cancer pain (BTcP). However, further examination is required to investigate the use of SFTs among the elderly. The aim of this study was to examine the influence of age in BTcP management with SFTs in the elderly population. Methods We performed subgroup analyses of a recently completed trial in two subsets of individuals: patients aged 65-74 years (low age group) and patients ≥ 75 years (high age group). Pain intensity (PI), onset of pain relief, frequency and duration of BTcP episodes, and adverse events (AEs) were assessed at 3, 7, 15, and 30 days. Health status instruments used were the Hospital Anxiety and Depression Scale (HADS-A and HADS-D) and the Short Form 12, version 2 (SF-12v2) questionnaire. Results Levels of PI at the end of the study improved significantly as compared with baseline in both the low and the high age groups (30.0% and 27.7% reduction, respectively). The onset of analgesia at the end of the study began in < 10 min in 85.0% of young-old subjects and in 62.5% of patients ≥ 75 years, but no significant differences were found. BTcP episodes lasted < 15 min in 75.0% of patients in the low age group and 58.3% in the high age group (p = 0.24). Most of patients in both groups experienced one to five BTcP daily episodes, at all assessment points. HADS-D decreased from 10.78 (± 4.33) to 8.21 (± 3.57) in the low age group, and from 10.96 (± 4.26) to 9.36 (± 3.35) in the high age group (p = 0.02). Significant differences in HADS-A scores from baseline to the end of the study were also observed in both subgroups (p < 0.05). Patients in the low age group had less favorable mental component summary (MCS) and physical component summary (PCS) scores than patients in the high age group. At the end of the study, 10.0% of young-old patients and 29.2% of patients aged ≥ 75 years reported AEs related to their treatment. The most commonly reported AEs included nausea, vomiting, constipation, somnolence, and skin disorders and they were generally mild to moderate in severity. Conclusions The results of this study showed that SFTs provided safe and clinically meaningful pain relief in both elderly subgroups. Clinical implications of these findings await validation in large, confirmatory studies to identify age subgroup divergences among elderly cancer patients treated with SFTs.